Research-Based Collective Activism Through the Production and Dissemination of Vodcasts About Environmental Pollution in the 8th Grade - Ana Rita Marques; Pedro Reis (Sisyphus, 2017)
The present research, involving a group of students from the 8th grade and the subjects of Natural Sciences and Information and Communication Technologies, had the purpose of studying the impact of the production and dissemination of vodcasts, subordinated to the theme of environmental pollution, in the perceptions of students regarding their capability for action and their development of activism skills. The construction of vodcasts by students, being usually associated with leisure and entertainment, can also be used as an activity for science teaching and learning. In this study, its production and subsequent dissemination was also used as a strategy for activism aimed at education and raising public awareness. The study followed a quail-quantitative approach, and is part of a larger investigation. The results show a positive evolution in students' perceptions regarding their capability for action, and the development of basic skills for research-based collective action.